Angola : Sixth Review Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Proposal for Post-Program Monitoring: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2012)
This report discusses Angola's sixth review under the Stand-By Arrangement (SBA) and request for waivers of nonobservance of performance criteria. Three years after the abrupt decline in world oil prices that severely impacted its economy, Angola has reached a sharply improved fiscal position, a more comfortable level of net international reserves, and a stable exchange rate. The authorities have embarked on far-reaching institutional reforms to enhance accountability in public spending and predictability in oil revenue transfers.